2016
DOI: 10.1111/jbg.12237
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic (co)variances of Gompertz growth function parameters in pigs

Abstract: The objective of this study was to estimate genetic (co)variances for the Gompertz growth function parameters, asymptotic mature weight (A), the ratio of mature weight to birthweight (B) and rate of maturation (k), using alternative modelling approaches. The data set consisted of 51 893 live weight records from 10 201 growing pigs. The growth of each pig was modelled using the Gompertz model employing either a two-step fixed effect or mixed model approach or a one-step mixed model approach using restricted max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…Therefore, when fitting a curve to a measured value of mature weight, should decrease as increases, and vice versa, resulting in a negative correlation between the two. This may explain why a negative correlation was consistently observed between these parameters in previous studies [8, 9] and the present study. Thus, the biological interpretation of the genetic correlation between growth curve parameters may be controversial.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, when fitting a curve to a measured value of mature weight, should decrease as increases, and vice versa, resulting in a negative correlation between the two. This may explain why a negative correlation was consistently observed between these parameters in previous studies [8, 9] and the present study. Thus, the biological interpretation of the genetic correlation between growth curve parameters may be controversial.…”
Section: Resultssupporting
confidence: 88%
“…Because parameter shifts the growth curve back and forth, setting the entry day as the initial day would affect the estimates of and its correlation with the other parameters. Similar contrasting results in genetic correlations were also found in two independent pig studies: Koivula et al [8] reported strong negative genetic correlations between and (− 0.80) and between and (−0.80) but a positive correlation between and (0.88), whereas Coyne et al [9] reported negative correlations between and (− 0.69) and between and (− 0.78) but a positive correlation between and (0.76). Although the estimates in the latter study [9] differed depending on the method used for estimation, a negative correlation between and was consistently observed.…”
Section: Resultssupporting
confidence: 76%
“…Recently , Forni et al (2009) estimated the growth curve parameters and genetic parameters simultaneously by one-step approach in beef cattle. In addition, Coyne et al (2017) reported the different results of genetic parameters between one-step and two-step approaches in pig population. The detailed studies on the genetic relationship between growth curve parameters and other economical traits by estimating in one-step approach have not been reported, and further study is necessary to characterize the methods in detail.…”
Section: Genetic Relationships Between Feed Efficiency Traits and Gromentioning
confidence: 99%
“…It is common, for example, in animal genetics (Emmans and Kyriazakis, 1997; Coyne et al, 2017), to use a parametric curve to describe observed growth trajectories of individual organisms. The interpretation of the curve is that the information contained in its parameters offers a low-dimension summary of serial and noisy data difficult to characterise per se.…”
Section: Methodsmentioning
confidence: 99%
“…Mathematical models are a common tool to characterise phenotype expression. In ontogenesis, for example, models are used to summarise or predict responses to environmental or dietary change via reaction norms (Stearns and Koella, 1986; Nussey et al, 2007; Dingemanse et al, 2010) or to describe growth traits, such as size, body composition, and metabolism via nonlinear relationships (Emmans and Kyriazakis, 2001; Coyne et al, 2017; Filipe et al, 2018). In this paper, we introduce a statistical approach to fit models to individual observations and to estimate individual- and population-level trait distributions.…”
Section: Introductionmentioning
confidence: 99%